Marxist ideology on Law - Amarasinghe, Kusal (International Journal of Research Publication and Reviews, 2021)
Marxist Philosophy can be interpreted as a theory that defines the historical evolution of human society. Marxist jurisprudence identifies the class struggle as the motivating force in history, in which the law and jurisprudence are not neutral but stand for the needfulness of the dominant class of the society. However, it is difficult to identify a Marxist theory of law. This paper tends to examine the Marxist approach to the law from a jurisprudential perspective.
Keywords: Class approach; Dialectical Materialism; Ideology; Law; Marxism